Development of an immunomagnetic nanoparticle-based lateral flow assay for detecting major kiwi allergen Act d1 in processed foods - Tsai, Wen-Che; Yin, Hsin-Yi; Leong, Weng-Tong; Tseng, Cheng-Yen; Wen, Hsiao-Wei (European food research & technology, 2022)
Kiwi is famous for its health-giving nutrients, but it is also a well-known allergenic fruit. In this work, an immunomagnetic nanoparticle-based lateral flow assay (IMNP-based LFA) is developed for detecting the major kiwi allergen, Act d1. Immunomagnetic separation by IMNPs is used to reduce the matrix effect and concentrate the target. Under optimized assay conditions, the visual limit of detection (vLOD) of the developed assay was 5 ng/mL Act d1 in the reaction buffer with a linear range from 5 to 1000 ng/mL. Its vLOD was estimated to be 25 ng/mL of Act d1 in juice and cookies. The assay exhibited favorable precision and reproducibility since the coefficient of variation (CV) values of inter-assay and intra-assay were all below 15%. Twenty-eight food samples were analyzed using the developed method, and the sensitivity and specificity of the assay in analyzing processed food samples were 85.7% and 100%, respectively. In summary, the developed IMNP-based LFA has potential to detect Act d1 residues in foods to protect people with a kiwi allergy from accidentally ingesting kiwi.